Use of multimodality imaging, histology, and treatment feasibility to characterize a transgenic Rag2-null rat model of glioblastoma - Jackson, Luke R.; Masi, Megan R.; Selman, Bryce M.; Sandusky, George E.; Zarrinmayeh, Hamideh; Das, Sudip K.; Maharjan, Surendra; Wang, Nian; Zheng, Qi-Huang; Pollok, Karen E.; Snyder, Scott E.; Sun, Phillip Zhe; et al. (Frontiers in Oncology, 2022)
Many experimental drugs that initially show potential in glioblastoma treatment in animal studies fail to translate to the clinic, contributing to a paucity of new therapeutic options available for patients with glioblastoma. While imaging is vital for the management of malignant brain tumors, cross-sectional molecular imaging is rarely utilized during the development of animal brain tumor models or for initial imaging biomarker determination. In this study, we aimed to develop an intracranial recurrent, drug-resistant, human-derived glioblastoma tumor in Sprague–Dawley Rag2-Rag2tm1Hera knockout rats and to characterize it histologically and using hybrid 18F-fluoroethyl-L-tyrosine (18F-FET) positron emission tomography (PET)/magnetic resonance imaging (MRI) (18F-FET PET/MRI). Histological analysis demonstrated human glioblastoma-like features of the intracranially implanted tumor, with rapid tumor cell proliferation (Ki67 positivity: 30.5 ± 7.8%). Immunohistochemical assessment for neovascularity (von Willebrand factor VIII) demonstrated varying positivity (1.8 to 5.0% positivity), indicating neovascular heterogeneity, which can be observed clinically in glioblastoma. Early serial MRI followed by simultaneous imaging using 18F-FET PET and chemical exchange saturation transfer (CEST) MRI (18F-FET PET/CEST MRI) demonstrated consistent, predictable tumor growth, with exponential tumor growth most evident between days 35 and 49 post-implantation. In a second, larger cohort of rats, 18F-FET PET/CEST MRI was performed in mature tumors (day 49 post-implantation) for biomarker determination, followed by evaluation of single and combination therapy as part of the model development and validation. The mean percentage of the injected dose per mL of 18F-FET PET correlated significantly with the mean %CEST when PET and MRI were performed simultaneously (r = 0.67, P < 0.05), demonstrating complementary information regarding the tumor cell demand for amino acids and tumor intracellular mobile phase protein levels. Finally, the use of this glioblastoma animal model for therapy assessment was validated by its increased overall survival after treatment with combination therapy (temozolomide and idasanutlin) (P < 0.001). Our findings hold promise for a more accurate tumor viability determination and novel therapy assessment in vivo.